2013
DOI: 10.1371/journal.pone.0052198
|View full text |Cite
|
Sign up to set email alerts
|

A Host Transcriptional Signature for Presymptomatic Detection of Infection in Humans Exposed to Influenza H1N1 or H3N2

Abstract: There is great potential for host-based gene expression analysis to impact the early diagnosis of infectious diseases. In particular, the influenza pandemic of 2009 highlighted the challenges and limitations of traditional pathogen-based testing for suspected upper respiratory viral infection. We inoculated human volunteers with either influenza A (A/Brisbane/59/2007 (H1N1) or A/Wisconsin/67/2005 (H3N2)), and assayed the peripheral blood transcriptome every 8 hours for 7 days. Of 41 inoculated volunteers, 18 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
218
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(227 citation statements)
references
References 40 publications
(55 reference statements)
8
218
1
Order By: Relevance
“…3B). This association between interferon activity and clinical signs is similar to what has been documented in the context of human influenza virus responses (23). Interferon transcriptional activity was not found to be correlated (R 2 ϭ 0.001) with peak body temperature, thus suggesting that day 5 interferon activity is more closely associated with fever duration rather than fever intensity.…”
Section: Resultssupporting
confidence: 82%
“…3B). This association between interferon activity and clinical signs is similar to what has been documented in the context of human influenza virus responses (23). Interferon transcriptional activity was not found to be correlated (R 2 ϭ 0.001) with peak body temperature, thus suggesting that day 5 interferon activity is more closely associated with fever duration rather than fever intensity.…”
Section: Resultssupporting
confidence: 82%
“…A detailed comparison of how different viral infections stimulate different immune responses can be done using data sets tracking the response of NHP PBMCs to Lassa virus infection (26) and influenza virus infection (40) and of human PBMCs to influenza virus infection (33,34,41). Already, preliminary direct analysis has shown that large parts of the initial response to each of these viruses are the same but that unique differences in initial gene expression during viral infections exist and can be predictive of specific infections (27).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression-based classifiers have also been shown to differentiate between specific viral etiologies, as demonstrated by a 70-gene RSV transcriptional profile that successfully separated infants with RSV lower respiratory tract infection from those with HRV or influenza virus infection with 94% sensitivity and 98% specificity (18). In addition to successfully distinguishing viral and bacterial infections, a gene expression-based classifier of viral infection has also demonstrated the ability to diagnose subjects very early, during the presymptomatic phase, and to allow eventual severity prediction (9).…”
Section: Current Gene Expression-based Disease Classifiersmentioning
confidence: 99%
“…Since gene expression is rapidly altered in many cell types in response to a variety of exposures (including infection), utilizing this information has several advantages. For example, host-based gene expression has been proven to be able to distinguish active infection from colonization (7), to distinguish among broad pathogen classes (such as distinguishing viral from bacterial pathogens), and to provide prognostic information and disease severity prediction (8,9). Furthermore, the widespread availability of quantitative reverse transcriptase PCR (qRT-PCR) platforms in clinical laboratories allows gene expression-based diagnostics to be more easily and directly translatable to patient care.…”
mentioning
confidence: 99%